Arizona Twin Project: A Focus on Early Resilience. (11th February 2013) - Lemery-Chalfant, Kathryn; Clifford, Sierra; McDonald, Kristy; O'Brien, T. Caitlin; Valiente, Carlos
Abstract : The Arizona Twin Project is an ongoing longitudinal study designed to elucidate the genetic and environmental influences underlying the development of early competence and resilience to common mental and physical health problems during infancy and childhood. Participants are a sample of 600 twins (25% Hispanic) recruited from birth records in the state of Arizona, United States. Primary caregivers were interviewed on twins' development and early social environments when twins were 12 and 30 months of age. Measures include indices of prenatal and obstetrical risk coded from hospital medical records, as well as primary caregiver-report questionnaires assessing multiple indicators of environmental risk and resilience (e.g., parental warmth and control, family and social support), twins' developmental maturity, temperament, health, behavior problems, and competencies. Preliminary findings highlight the importance of the early environment for infant and toddler health and well-being, both directly and as a moderator of genetic influences. Future directions include a third longitudinal assessment in middle childhood examining daily bidirectional relations between sleep, health behaviors, stress, and mood.